Functional outcome and result of intra-articular injection hyaluronic acid in treatment of osteoarthritis of knee - Chaudhary, Deepak; Khan, Yasir Ali (International Journal of Research in Medical Sciences, 2016)
Background: Osteoarthritis (OA) is the most common disease of joints in adults around the world. Worldwide, it is estimated to be the fourth leading cause of disability. Objective of the study was to assess functional outcome and results of injection of hyaluronic acid in symptomatic osteoarthritis knee. Methods: It was a prospective clinical study with 3 months of follow-up. Clinically proven sixty patients of osteoarthritis knee (OA) included in study according to inclusion and exclusion criteria on OPD basis after getting written and informed consent, treated by weekly intra articular injection of Hyaluronic acid (20 mcg/2ml) in affected knee joint for 5 weeks by single author . Functional outcome and clinical assessment was done by pain at visual analogue score (VAS) and by knee range of movements, patients global assessment of treatment and physician global assessment of treatment. The occurrences of adverse events were also assessed at 3 month. Results: Sixty patients participated in study and reported statistically significant improvement in VAS score in mild and moderate osteoarthritis of knee from 4.46±0.52 and 6.57±0.72 points respectively pre-treatment level to 2.26±0.43 and 4.36±0.24 points respectively at three months post Hyaluronic acid injection follow up, improvement in joint tenderness and patients & physician’s global assessment score also improved significantly clinically as well as statistically in mild to moderate group while in severe group no clinical and statistically significant improvement was observed in any parameters, change in range of motion at three months was not significant in any group. Conclusions: Visco-supplementation with intra articular injection hyaluronic acid should be considered as safe and effective modality of treatment in selected group of mild to moderate osteoarthritis before mechanical changes takes place and patient complies with regular exercise, weight control and postural habits.